THE INFLUENCE OF RICE BRAN ON THE BREAD-MAKING PROPERTIES OF WHEAT FLOUR - Boldina A.A.; Sokol N.V.; Sanzharovsckaya N.S. (Техника и технология пищевых производств)
Development of new formulas and technologies of bakery and flour confectionery of high nutrition value is advantageous for the food industry. The increase of bakery product assortment is due to the use of additional raw materials, one of which is rice bran. The rice bran selected at the Krasnodar Territory rice mills was used as the object of research. The aim of the research was to study the effect of rice bran on protein-proteinase and carbohydrate-amylase complexes of wheat flour for justification of its introduction in bakery and the gluten-free flour confectionery of a functional purpose. In the presence of the studied supplement there are changes of starch properties, quantity and quality of wheat flour gluten and structural and mechanical characteristics of the dough. Assessment of the influence of rice bran on flour baking properties and physical properties of the dough resulted in the technological decision on the use of an intensive kneading in the course of which 10 and 15 per cent supplement is recommended to be brought in for ensuring functional properties of the product.